The Great Brain. - Fitzgerald, John Dennis; Mayer, Mercer, 1943- (New York : Dell Pub. Co., 1979)
The exploits of the Great Brain of Adenville, Utah, are described by his younger brother, frequently the victim of the Great Brain's schemes for gaining prestige or money.
Reprinted by arrangement with The Dial Press.
Keywords: Humorous stories; Utah -- Fiction